Pengaruh Pendidikan Kesehatan Tentang Dismenore Melalui Media Booklet Terhadap Tingkat Pengetahuan, Perilaku, Dan Daya Terima Siswi Di Smk Surakarta - Nurmusazanah, Esti; , Yuli Kusumawati, SKM., M. Kes (Epid); , Kusuma Estu Werdani, SKM., M.Kes (2015)
Dysmenorrhea is a menstrual blood flow disorders or menstrual pain. Dysmenorrhea treatment with drug therapy non steroidal anti prostaglandin plays a very important for primary dysmenorrhea, including Indometason, Ibuprofen, and Naproksen. The purpose of this study was to analyze the effect of health education on dysmenorrhea through the media booklet on the level of knowledge, attitudes, and acceptance of students in SMK. This research is a quasi-experimental (Quasi Experiment) with a pretest-posttest design with Control Group and Experimental Pre-plan Posttest Only Design. The population in this study all female student were X and XI in SMK as many as 807 student. Selection of the sample using simple random sampling method, were divided into three groups: the experimental group in SMKN 4, the control group in SMKN 7, and the group received power in SMK Batik 1 Surakarta with 135 samples. Statistical test using Paired sample t-test, showed no difference in the average score of knowledge (p = 0.000) and behavior (p = 0.000) in the experimental group after treatment and there was no difference in mean score of knowledge (p = 0.000) and behavior (p = 0.000) in the control group. The test results Independent sample t-test showed no difference in the effect of health education on dysmenorrhea between using booklets and LCD for knowledge (p = 0.127) and behavior (p = 0.198) in the treatment of dysmenorrhea girls. For teens acceptance of the booklet, almost respondents particularly like the booklet as many as 23 respondents (51,1%).